2018
DOI: 10.1039/c8nj00558c
|View full text |Cite
|
Sign up to set email alerts
|

Solvatochromism and fluorescence response of a halogen bonding anion receptor

Abstract: Herein, we present on two 2,6-bis(4-ethynylpyridinyl)-4-fluoroaniline receptors that display solvatochromic absorption and emission. Neutral derivatives displayed opposite solvatochromic behavior as compared to the alkylated receptors. Adding anions induced changes in the absorption and emission spectra. In general, the fluorescence of the halogen bonding receptor was quenched less efficiently when compared to the hydrogen bonding receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Acyclic fluorescent XB sensors based on other XB donor motifs include, for example, iodo-naphthoquinone receptors for sensing of SO 4 2− in ACN 116 and iodo-pyridinium receptors for sensing of various halides and oxoanions in DCM. 117 …”
Section: Optical Sensorsmentioning
confidence: 99%
“…Acyclic fluorescent XB sensors based on other XB donor motifs include, for example, iodo-naphthoquinone receptors for sensing of SO 4 2− in ACN 116 and iodo-pyridinium receptors for sensing of various halides and oxoanions in DCM. 117 …”
Section: Optical Sensorsmentioning
confidence: 99%
“…There are two relevant papers. Berryman et al reported the synthesis and anion-binding properties of receptor 1 (2,6-bis(4-ethynylpyridinyl)-4-fluoroaniline) which can act as a halogen donor, trapping a wide variety of anions (Cl − , Br − , I − , SCN − , NO 3 − , HSO 4 − , H 2 PO 4 − and ReO 4 − ) [40] (Scheme 1). The presence of intramolecular N–H···I hydrogen bonds (HBs) increases the strength of the I···anion halogen bonds (XBs).…”
Section: Introductionmentioning
confidence: 99%
“…Initially, halogen bonding had primarily been explored in crystal engineering [16][17] and in the gas phase; [18][19] however, further investigation of these interactions have focused on their efficacy in solution phase as well. [20][21][22][23] Halogen bonding interactions are comparable in strength to those of hydrogen bonding, and furthermore, they demonstrate a surprising resilience to interference from competitive, polar solvents. [24][25][26] These attributes have generated a growing interest in halogen bonding from the supramolecular community over the past 20 years.…”
mentioning
confidence: 99%